Building The House of The Nation’s Civilization with Peace as The Foundation - Mutaqi, Ahmad Saifudin (Universitas Islam Indonesia, 2021)
Resistance to Indonesia's diversity can still be seen in the various incidents of intolerance and discrimination that occurred with political and religious backgrounds. There have been a number of issued government regulations that led to various interpretations and resulted in unjust public services, especially for some minority groups. It is not necessary for the government to impose restrictions on a person's basic religious practices or beliefs and regulate what kind of clothing a woman should wear, nor do they need to regulate what the physical form of a place of worship should be. Likewise, fellow citizens who interpret these regulations by themselves have the potential to decrease the public order. Hence the role of the state officials in enforcing the law is very important to achieve a peaceful society. Culturally, the reconciliation mechanisms in society can be developed when there is a desire to carry out a healthy dialogue. People are used to talking about different basic matters and they are respecting these differences so that they can work together for the benefit of the society. Dialogue is a communication process that considers semantic and pragmatic principles, where conversations with mutual understanding, acceptance, peaceful life and cooperation for mutual prosperity will arise. The atmosphere of a peaceful life is an important foundation for constructing a